IS CASTING AN ACCEPTABLE TREATMENT APPROACH FOR A DISTAL RADIUS FRACTURE THAT HAS UNDERGONE A SATISFACTORY CLOSED REDUCTION? - Khalid Masood; Muhammad Jamil; Farooq Ibrahim Pasha (Journal of University Medical & Dental College, 2013)
Objective: To evaluate the radiographic outcome in fractures of the distal radius treated with closed reduction and plaster casting. Design: A retrospective study Setting: Hand and Upper limb Surgery Centre and Combined Military Hospital Lahore Pakistan. Patients: Forty three patients (31 males, 12 females, aged 18-75 years), with fractures of distal radius were seen between January 2011 and December 2011. Interventions: Closed reduction and plaster casting of fractures, followed up by good-quality postero-anterior and lateral radiographs to evaluate stabilization and healing. Main outcome measures: Radial height (length), radial inclination and volar (palmar) tilt were measured on radiographs obtained preoperatively, immediately postoperatively, and at the time of removal of plaster cast. Data were analyzed by the t-test. Results: There was an acceptable improvement in the measurements of radial height and radial inclination immediately after closed reduction and stabilization with plaster cast. This improvement was gradually lost and height and inclination were significantly decreased by the time plaster was removed. Improvement in volar tilt was not significant. Results were poor in AO type B and C and acceptable in AO type A fractures. Conclusion: Closed reduction and plaster casting is a common method to deal with bone fractures but cannot effectively protect comminuted distal radial fractures from loss of reduction, which may be associated with shortening and re-displacement and malunion.